(untitled) (Literary Voice, 2024)
The paper is a critical exploration of the fluidity of becoming through the character of Robin in Claudia Morgado Escanilla’s short film No Bikini1 (2007). The paper further investigates the role of water in the dynamic configurations of the paradigms of gender expressions and highlights Robin’s relationship with water in their process of ‘becoming.’ An extensive focus on the stylistic construction of Robin’s character and the space of the swimming pool is analysed in rendering further possibilities of extending one’s self beyond the realms of the heteronormative world. Hence, this paper essays at understanding the positionality of children amidst the larger queer expressions predominantly constitutive of adult lives, and how children negotiate gender roles and a child’s casual manner of queering heteronormative structures, are further studied.